2022
DOI: 10.3233/jpd-212923
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabis in Parkinson’s Disease: A Systematic Review and Meta-Analysis

Abstract: The legalization of cannabis in many countries has allowed many Parkinson’s disease (PD) patients to turn to cannabis as a treatment. As such there is a growing interest from the PD community to be properly guided by evidence regarding potential treatment benefits of cannabis. This systematic review and meta-analysis aims to compile the best available evidence to help guide patients and their family, clinicians and researchers make informed decisions. A systematic search of the literature was conducted in June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Analysis of clinical meta-data offers mixed evidence in support of medical cannabis. While well tolerated, medical cannabis has been shown to have limited benefit in improving dyskinesia and motor function (Thanabalasingam et al, 2021), although patients did report improvements in sleep quality and quality of life (Urbi et al, 2022). Conversely, cannabis-derived phytocannabinoids have shown a clear neuroprotective effect in rodent models (Prakash and Carter, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of clinical meta-data offers mixed evidence in support of medical cannabis. While well tolerated, medical cannabis has been shown to have limited benefit in improving dyskinesia and motor function (Thanabalasingam et al, 2021), although patients did report improvements in sleep quality and quality of life (Urbi et al, 2022). Conversely, cannabis-derived phytocannabinoids have shown a clear neuroprotective effect in rodent models (Prakash and Carter, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search of the literature, conducted in June 2021 [ 55 ], presented five RCT and eighteen nonrandomized studies investigating cannabis treatments in PD patients. According to the authors, although no compelling evidence was found to recommend the use of cannabis in PD patients, a potential benefit was identified with respect to alleviation of PD-related tremor, anxiety, pain, improvement of sleep quality and quality of life.…”
Section: Cbd and Parkinson's Diseasementioning
confidence: 99%
“…There are reports of motor and non-motor benefits in PD. But natural and synthetic cannabinoids have not shown significant effects in controlled clinical trials ( Thanabalasingam et al, 2021 ; Urbi et al, 2022 ), and there is insufficient evidence for cannabis products as adjunctive dopaminergic therapy.…”
Section: Cannabinoidsmentioning
confidence: 99%